Aberration in monocyte count as anticipator of adverse terminal events in COVID-19: case-control study - Shaheed Mohammed, Haider; M. Hussein, Methaq A. (AVFT – Archivos Venezolanos de Farmacología y Terapéutica, 2021)
Background: Aberrancy in monocytes account is customarily recognized in patients with COVID-19 strikingly in gravely affected patients, the exacting interrelation with detrimental consequences still in the gap. The study was carried out to found any significant monocyte level changes in COVID-19 and its relation to diagnostic usefulness and expectation of adverse outcomes. A sample of 100 patients was recruited into the analysis; all with diagnosis compatible with pneumonia underwent care inwards of Al-Hussein Hospital for isolation; 50 participators with COVID-19 as cases and 50 participators with influenza A elected control. The diagnosis was suggested by clinical and radiological attributes and verified by polymerase chain reaction. Monocytes total and laboratory analysis of inflammatory indices and organ vitality were achieved for all participants. The mean age was 64.4, including 56 males and 44 females. 66% of cases were monocytopenic, 34% were non-monocytopenic. 12% of control were monocytopenic while 88% were non-monocytopenic with significant difference (P value=0.001). Forty-five participants were critical while 55 were non-critical, 37 COVID-19, and eight controls were critical and admitted to the ICU. Forty-one participants died, 35 from the COVID-19 category and six from controls. 30 of COVID-19 who were critical in ICU were monocytopenic (all died), three were non-monocytic (only one died) and 4 had monocytosis (all died), 6 of control who were critical in ICU were monocytopenic (all died), 2 had normal count (all survived) and no one had monocytopenia (Odd ratio=1.200). Deviation in monocyte count from the norm is a valuable discriminator for the diagnosis of COVID-19 and a suitable anticipator across all spectrums for its adverse consequences.